A Study of Using Thai Words in Comparing with the Meaning of Chinese Resultative Complements - Theerapojjanee, Theerawat (Journal of Sinology (วารสารจีนวิทยา), 2014)
One of Thai learners’ problems in using Chinese resultative complements is that Thai learners are neither able to cope with the sub-meaning in Chinese complements nor able to look for the suitable word to compare with Thai, and sometimes they cannot select the close meaning complements to use. This article aims to study the sub-meaning and the using of Thai words comparing with high-frequency Chinese resultative complements, in order to propose the guideline in teaching Chinese resultative complements to Thai learners.